1997
DOI: 10.1073/pnas.94.26.14865
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids: Deficient cognitive performance in aged rats depends on low pregnenolone sulfate levels in the hippocampus

Abstract: Pregnenolone sulfate (PREG S) is synthesized in the nervous system and is a major neurosteroid in the rat brain. Its concentrations were measured in the hippocampus and other brain areas of single adult and aged (22-24 month-old) male Sprague-Dawley rats. Significantly lower levels were found in aged rats, although the values were widely scattered and reached, in about half the animals, the same range as those of young ones. The spatial memory performances of aged rats were investigated in two different spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
146
1
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(152 citation statements)
references
References 39 publications
(42 reference statements)
2
146
1
3
Order By: Relevance
“…Inhibition of de novo synthesis of neurosteroids reduced dendritic spine formation in Purkinje cells in organotypic slice cultures (Sakamoto et al, 2002) and remyelination of damaged nerves by Schwann cells (Koenig et al, 1995). In addition, low hippocampal levels of pregnenolone sulfate correlate with poor performance in memory tasks by rodents (Vallee et al, 1997). Administration of neurosteroids has been proposed as a therapeutic treatment for various pathologies such as seizure disorders and memory loss attributable to aging (Akwa et al, 2001; for review, see Mellon and Griffin, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of de novo synthesis of neurosteroids reduced dendritic spine formation in Purkinje cells in organotypic slice cultures (Sakamoto et al, 2002) and remyelination of damaged nerves by Schwann cells (Koenig et al, 1995). In addition, low hippocampal levels of pregnenolone sulfate correlate with poor performance in memory tasks by rodents (Vallee et al, 1997). Administration of neurosteroids has been proposed as a therapeutic treatment for various pathologies such as seizure disorders and memory loss attributable to aging (Akwa et al, 2001; for review, see Mellon and Griffin, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in levels of locally produced neurosteroids in the hypothalamus, hippocampus, and other regions may serve as crucial paracrine modulators of essential brain functions, including sexual drive, learning, and memory (Majewska et al, 1986;Genazzani et al, 1995;Frye et al, 1996;Calogero et al, 1998;Akwa et al, 2001). Deficits in neurosteroid production may contribute to a variety of disorders, including dementia, epilepsy, premenstrual syndrome, and postpartum depression (Vallee et al, 1997;Smith et al, 1998;Beyenburg et al, 1999). Consequently, it is critical that we understand the mechanism of neurosteroid biosynthesis and regulation.…”
mentioning
confidence: 99%
“…Among them, the neurosteroid pregnenolone sulfate (3␤-hydroxy-5-pregnen-20-one sulfate, PREGS) has been well described as a potent steroidal enhancer of learning and memory processes in rodents (1)(2)(3)(4)(5)(6). Of particular interest is the physiological role of PREGS in the hippocampus, which was recently demonstrated for the preservation of age-related spatial memory loss (4).…”
mentioning
confidence: 99%
“…Finally, it is possible that PS preferentially affects the hippocampus. Studies on the effect of PS on learning and memory suggested that limbic structures are particular targets of action of PS (Flood et al, 1995;Vallee et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampus was chosen as the site for PS infusion for several reasons. PS is present in high concentrations in the hippocampus (Wang et al, 1997) and can modulate learning and memory function when infused into this structure (Flood et al, 1995;Vallee et al, 1997). Moreover, the hippocampus has long been implicated in temporal lobe epilepsy and is the focus for investigation into the basic mechanisms of epileptogenesis (McNamara, 1999).…”
Section: Introductionmentioning
confidence: 99%